2022
DOI: 10.1021/acsearthspacechem.1c00323
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Adsorption Processes at Clay Mineral Surfaces: A Coupled Experimental and Modeling Approach

Abstract: Quantification of adsorption processes on clay mineral surfaces is often necessary to predict the extent and the evolution of contaminants’ migration in surficial and underground environments. Many studies have been dedicated to retention measurement as a function of pH and ionic strength in relation with the two main identified adsorption processes for clay minerals, that is, cation exchange on their basal surfaces and surface complexation on their edge surfaces. The latest process has been repeatedly assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Nevertheless, we consider that our cis-vacant model is improved compared to the previously published trans-vacant model by Tournassat et al, because a good agreement between predicted and measured proton charge was found (Figure ) and because our cis-vacant model takes into account the most recent insights on clay edge surface structure and reactivity. First, the cis-vacant structure at montmorillonite edges was confirmed with high resolution electron transmission microscopy measurements . And second, relative proportions of edge surface directions were made available from AFM measurements .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, we consider that our cis-vacant model is improved compared to the previously published trans-vacant model by Tournassat et al, because a good agreement between predicted and measured proton charge was found (Figure ) and because our cis-vacant model takes into account the most recent insights on clay edge surface structure and reactivity. First, the cis-vacant structure at montmorillonite edges was confirmed with high resolution electron transmission microscopy measurements . And second, relative proportions of edge surface directions were made available from AFM measurements .…”
Section: Resultsmentioning
confidence: 99%
“…First, the cis-vacant structure at montmorillonite edges was confirmed with high resolution electron transmission microscopy measurements. 34 And second, relative proportions of edge surface directions were made available from AFM measurements. 54 Our cis-vacant model could be further improved with the addition of other types of substitutions, of which the p K a values remain to be determined using FPMD calculations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past several decades, the adverse impacts of heavy metals and organic pollutants on animals and plants have been studied and discussed extensively, and it has become clear that the treatment of water containing heavy metals requires urgent attention (Wang et al , 2006). Clay materials play a significant role in the adsorption of heavy metals in water due to their large surface areas and charged surfaces (Gomes et al , 2021; Orucoglu et al , 2022; Xu et al , 2022). Previous studies have shown that a given heavy metal can be adsorbed by several clay minerals (Liu, 2005; Erdoğan et al , 2021; Ma et al , 2021; Sarabadan et al , 2021; Silva et al , 2021; Barrientos-Velazquez et al , 2022; Werling et al , 2022).…”
mentioning
confidence: 99%